Hard call : great decisions and the extraordinary people who made them - McCain, John, 1936-2018 (Twelve, 2007)
At some point in our lives, we all face tough decisions and have to make that hard call. In this book, Senator McCain and Mark Salter use experiences of both extraordinary people and people in extraordinary circumstances to describe the anatomy of a great decision. Highlights include: Henry Ford's decision to sacrifice his company's competitive edge by reducing the work day and guaranteeing a minimum wage; Branch Rickey's decision to offer Jackie Robinson a contract to play for the Brooklyn Dodgers in the face of public opposition; Ellen Johnson-Sirleaf 's decision to return to wartorn Liberia after receiving an economics degree from Harvard; General Fred Weyand's decision to redeploy fifteen of his battalions despite resistance from senior American military commanders in Vietnam; and much more.--From publisher description.